2020
DOI: 10.1530/erp-19-0057
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic RV-E/e′ for predicting right atrial pressure: a review

Abstract: Right atrial pressure (RAP) is a key cardiac parameter of diagnostic and prognostic significance, yet current two-dimensional echocardiographic methods are inadequate for the accurate estimation of this haemodynamic marker. Right-heart trans-tricuspid Doppler and tissue Doppler echocardiographic techniques can be combined to calculate the right ventricular (RV) E/e’ ratio – a reflection of RV filling pressure which is a surrogate of RAP. A systematic search was undertaken which found seventeen articles that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We also found that there was no significant difference in the PVPR between patients with HF in sinus rhythm and patients with AF. This indicated that there was no correlation between AF and high RAP, which is in agreement with the findings of a previous study[ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that there was no significant difference in the PVPR between patients with HF in sinus rhythm and patients with AF. This indicated that there was no correlation between AF and high RAP, which is in agreement with the findings of a previous study[ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…With respect to the assessment of right ventricular diastolic function, there is no widely accepted gold standard. Tricuspid valve E/A ratio, E/e’ ratio and DT (E wave decelerate time) are the parameters most commonly used for the assessment of RV diastolic function and the tricuspid E/A ratio, E/e’ ratio has been shown to correlate well with cardiovascular outcome and thus have immense clinical relevance [ 9 , 10 , 22 , 23 ]. In the multivariate regression analysis, it was found that the Tei’- index showed a significant correlation with the E/e 'and DT, which representing the early diastolic function, indicating that the new index was more effective in evaluating RV early diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a reasonable diagnostic ability of RV-E/e′ for estimating RAP in patients with coronary artery disease and RV systolic dysfunction [34] , [37] , [38] , [39] . The diagnostic ability of RV-E/e′ was generally poor in studies of pediatrics, heart failure and mitral stenosis [35] , [36] , [40] , while the results were equivocal in other diseases [41] . Bland–Altman analyses showed good accuracy but poor precision of RV-E/e′ for estimating RAP [34] , [36] .…”
Section: Ra Pressuresmentioning
confidence: 95%